Ethnobotany and Shruby Diversity in Homegardens of Cherpu Block, Kerala, India - Vijayan, Anju S.; Gopakumar, S. (Indian Forester, 2015)
A survey was conducted in the home gardens of Cherpu block in Thrissur district of Kerala state to elucidate the floristic attributes of the shrub species and to document the associated ethnobotanical information. Plant diversity analyses revealed 23 shrub species distributed in 15 families in the homegardens. These were observed to be useful in everyday life of the local inhabitants of village as medicinal, edible, ornamental, fuel wood and other uses. Most of the shrubs recorded, having more than one uses. High shrub diversity of Cherpu block may be due to less interference of monoculture crops and plantation species.